STUDY ON THE ABILITY OF USING QUESTION TAGS BY THE SECOND SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Ratnasari Ratnasari; M. Syarfi M. Syarfi; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was aimed at finding out the ability of using question tags by the second semester students of English Study Program FKIP Universitas Riau. The population of this research was the second semester students of English Study Program FKIP Univeristas Riau. The number of the sample was 37 students selected by using cluster random sampling technique. The instrument to collect the data was multiple choice test items with 50 questions. The data were analyzed by classifying them into five levels of ability: very poor, poor, mediocre, good and excellent. The finding of this study tells that there are 12 students (32,43%) are in excellent level, 21 students (56,75%) are good in level, 3 students (8,10%)are in mediocre level and 1 student (2,70%) is in poor level. Based on the finding of the research, it was found that the students’ ability of using question tags by the second semester students of English Study Program FKIP Universitas Riau was in good level with the mean score was 72. The implication of this research is that the second semester students of English Study Program FKIP Univeritas Riau have a good ability in using question tags.Key Words: Students’ ability, Study, Question Tags